PENGARUH SISTEM INFORMASI AKUNTANSI PENJUALAN DAN PENGENDALIAN INTERNAL TERHADAP EFEKTIVITAS PENGENDALIAN PIUTANG PADA PT NIAGA INTER SUKSES PEKANBARU - TRI ASTUTY BR HASIBUAN; ASEPMA HYGI PRIHASTUTI; RAHMI ZAINAL (JURNAL AKUNTANSI DAN KEUANGAN, 2022)
This study aims to examine the effect of Sales Accounting Information System and Internal Control on the Effectiveness of Receivable Control at PT. Niaga Inter Sukses Pekanbaru which is engaged in cargo. The sample selection used purposive sampling method with a sample of 35 people who are employees of the sales accounting department, consisting of 26 Sales, Accounts Receivable 1 person, Stock Administration 1 person, Sales Administration 3 people, Finance 2 people, and Warehouse 2 people. Data analysis used Multiple Regression with SPSS Program. The results showed that the Sales Accounting Information System (X1) had a positive and significant effect on the Effectiveness of Accounts Receivable Control (Y), Internal Control (X2) had a positive and significant effect on the Effectiveness of Receivable Control (Y), and together the Sales Accounting Information System (X1) and Internal Control (X2) affect the Effectiveness of Receivable Control (Y).